2019
DOI: 10.4103/wjnm.wjnm_59_18
|View full text |Cite
|
Sign up to set email alerts
|

Gallium-68 prostate-specific membrane antigen positron emission tomography/computed tomography compared with diagnostic computed tomography in relapsed prostate cancer

Abstract: The aim of this study was to evaluate if prostate-specific membrane antigen (PSMA) positron emission tomography/computed tomography (PET/CT) has a higher detection rate compared to standard contrast CT imaging for patients with a rising prostate-specific antigen (PSA) following definitive treatment (i.e., curative radical prostatectomy, radiotherapy, and brachytherapy) for prostate cancer in a private hospital setting. A retrospective single-site clinical audit was conducted on 150 PSMA PET/CT scans done for p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…The prostate-specific membrane antigen (PSMA) is a membrane-specific type II glycoprotein that is overexpressed in more than 80% of PCA cells and is therefore an ideal target for diagnostic imaging [5,6]. Recently Gallium-68-labelled PSMA PET computed tomography (PSMA-PET/CT) was found to be superior in localizing actively metabolizing tumor in patients with primary diagnosis or recurrence of PCA compared to conventional imaging modalities and choline-based PET/CT [7][8][9][10][11]. The detection rates for PSMA-PET/CT reported in the literature vary from 46% to 97% depending on the levels of prostate-specific antigen (PSA) [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prostate-specific membrane antigen (PSMA) is a membrane-specific type II glycoprotein that is overexpressed in more than 80% of PCA cells and is therefore an ideal target for diagnostic imaging [5,6]. Recently Gallium-68-labelled PSMA PET computed tomography (PSMA-PET/CT) was found to be superior in localizing actively metabolizing tumor in patients with primary diagnosis or recurrence of PCA compared to conventional imaging modalities and choline-based PET/CT [7][8][9][10][11]. The detection rates for PSMA-PET/CT reported in the literature vary from 46% to 97% depending on the levels of prostate-specific antigen (PSA) [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Some authors observed detection rates of >50% in patients with PSA <0.5 ng/mL [ 16 , 17 ]. Such a high sensitivity allows identification of very early recurrences with lesions <5 mm in size [ 10 ].…”
Section: Introductionmentioning
confidence: 99%